Romantic Transfer from Thermodynamic Theories to Personal Theories of Social Control: A Randomised Controlled Experiment - Chen Chen; Si Chen; Helen Haste; Robert L. Selman; Matthew H. Schneps (MDPI AG, 2023)
The transfer of learning is arguably the most enduring goal of education. The history of science reveals that although numerous theories have been transferred from the natural sciences to the socio-political realm, educational practitioners have often deemed such transfers romantic and rhetorical. We conducted an experiment that randomly assigned a sample of 292 college freshmen in China to two groups to learn different thermodynamic theories: entropy or self-organization theory. We examined whether the two groups may arrive at different implications about social (and government) control without explicit instructions. We found that participants who learned the theory of entropy were more likely to believe the social system would become chaotic over time without external control; thus, they preferred tightened social control. Whereas participants who learned self-organisation theory were more likely to believe that order may form from within a social system; therefore, they downplay external control and prefer stronger individual agency. Follow-up interviews showed that the participants' narratives about social control were largely consistent with the thermodynamic concepts they had learned. Our findings have critical implications for the recent trend in STEM education that promotes the teaching of cross-cutting concepts-seeking patterns from interdisciplinary ideas-that may implicitly prime students to borrow physical science theories to formulate personal social hypotheses and engage in moral-civic-political discourse.